When an Event Is Perceived Depends on Where We Attend. (June 2019) - Jovanovic, Ljubica; Mamassian, Pascal
Does the moment when an event is perceived depends on where it is presented? To measure when participants perceived events, they were first familiarized with trial duration, by watching the hand of a clock rotating. Then, the hand was removed, and stimuli were presented at a random time from the trial onset. Participants indicated the location where the hand would have been when the stimulus was presented. The stimuli's eccentricity, the appearance, and location of the spatial features of the clock were varied. The targets were reported earlier if they were presented in spatial proximity to the clock outline, even when it was not presented during the trial. The effect was replicated with stimuli presented at the same distance from fixation but at different distances from the spatial features. In summary, the time of an event is perceived earlier if it is presented near attended features in the visual scene.